A systematic literature review on the economic impact of digitalization technologies in transport logistics - Navid Julian Sardarabady; Susanne Durst (Transport Economics and Management)
In the domain of transport logistics, digitalization technologies are recognized as a high priority, demanded by stakeholders such as legislators, customers, and partners. Concurrently, the industry contends with escalating challenges, including persistent cost pressures and emergent crises such as pandemics and geographical conflicts. To address these multifaceted challenges, the transport logistics sector seeks solutions through the adoption of digitalization technologies. Nevertheless, the widespread implementation of these technologies, often associated with substantial investment costs, necessitates clear evidence of transparent economic benefits and potential remedies for current crises. In order to enhance the understanding of the economic impact of digitalization technologies in transport logistics, this paper presents a state-of-the-art systematic literature review (SLR). The review encompasses 64 papers from leading journals, providing an insightful overview of the field's thematic diversity and developmental trajectory. Employing content analysis, the study reveals emerging themes. Key findings indicate that the research field is still in its early stages but is experiencing discernible growth, with a significant focus on emerging technologies. Finally, several promising future research areas and possible research questions are identified based on these findings.